Are e-cigarettes really a healthier alternative to smoking? - Zwoliński, Michał; Zemsta, Katarzyna; Szuleka, Marta; Sobota, Weronika; Kamińska-Omasta, Katarzyna; Piskorz, Przemysław; Kulesza, Bartłomiej; Tomasiuk, Ryszard (Family Medicine & Primary Care Review, 2024)
E-cigarettes emerged in the early 21st century as a safer health alternative to conventional cigarettes. E-cigarettes use e-liquids based on glycerine and propylene glycol. This results in smaller amounts of toxic substances in the aerosol they produce compared to traditional cigarettes. The rather short existence of such replacements does not make it clear whether they are actually better for smokers’ health. The increasing number and younger age of smokers has prompted researchers to expand their research on the subject. A review of literature has shown that e-cigarettes affect many biochemical mechanisms, affecting the health of their users. They cause oxidative stress and, consequently, a cytotoxic effect; an increase in the production of mucins, taking part in lung diseases; affect the formation of DNA damage, carcinogenesis, sensitivity to chemotherapy, inflammatory response and disrupt cytokine levels in tissues. In addition, they cause thinning of the laryngeal mucosa, autophagy of middle ear epithelial cells, apoptosis of gingival fibroblasts, weakening of the tooth attachment apparatus and promote dental caries. It will take some time to test the theory of whether e-cigarettes are a healthier substitute for classic cigarettes, but based on current knowledge, one should be aware that these substances can cause adverse health effects.